Estimation of penetration-related X-band elevation bias in Polar Regions -- A study over the Northern Greenland Ice Sheet and the Devon Island Ice Cap - Abdullahi, Sahra; Wessel, Birgit; Huber, Martin; Wendleder, Anna; Roth, Achim (2020)
Ongoing global warming causes dramatic changes globally, especially with respect to Polar Regions. In this context, digital elevation data is of high importance for most glaciological applications. In this paper, we investigate TanDEM-X penetration depth over snow and ice on the Devon Ice sheet. In particular, the relation of backscatter intensity and interferometric coherence to penetration depth of the X-band InSAR signal is explored in order to improve the reliability of TanDEM-X elevation data. A model that has been contrainted on Northern Greenland was transfered to Devon ice cap. With the help of experimental test data and elevation reference data in Devon Island we demonstrated the transferability of this method of TanDEM-X penetration bias estimation.